2018
DOI: 10.1038/s41598-018-32478-z
|View full text |Cite
|
Sign up to set email alerts
|

Distinct profile and prognostic impact of body composition changes in idiopathic pulmonary fibrosis and idiopathic pleuroparenchymal fibroelastosis

Abstract: Change in body composition with skeletal muscle wasting, a major component of pulmonary cachexia, is associated with mortality in chronic obstructive pulmonary disease and cancer. However, its relevance in interstitial lung diseases (ILDs) remains unclear. We hypothesized changes in body composition would be associated with mortality in ILDs. We measured the cross-sectional-area (ESMCSA) and muscle attenuation (ESMMA) of erector-spinae muscles, as determined by CT-imaging, in patients with idiopathic pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
74
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 34 publications
5
74
1
Order By: Relevance
“…Evaluation of the nutrition status with BMI was essential in prognosis of other pulmonary disease patients including the chronic obstructive pulmonary disease and the nosocomial infection. (26)(27)(28)(29) The present study suggested that the gender of females might be risk for the prolonged hospitalization. The reason why the hospitalization stay tended to be long in the aged females pneumonia patients was not clear, (30) as the number of the patients with good performance status (0 + 1) was not different between males (14 cases) and females (13 cases) and there was no significance difference between the genders regarding the other factors evaluated in the present study.…”
Section: Discussionmentioning
confidence: 53%
“…Evaluation of the nutrition status with BMI was essential in prognosis of other pulmonary disease patients including the chronic obstructive pulmonary disease and the nosocomial infection. (26)(27)(28)(29) The present study suggested that the gender of females might be risk for the prolonged hospitalization. The reason why the hospitalization stay tended to be long in the aged females pneumonia patients was not clear, (30) as the number of the patients with good performance status (0 + 1) was not different between males (14 cases) and females (13 cases) and there was no significance difference between the genders regarding the other factors evaluated in the present study.…”
Section: Discussionmentioning
confidence: 53%
“…The compound deposition/release rate in adipose tissue depends on tissue volume [ 29 , 30 ]. Loss of adipose and muscle tissue is often observed in cancer, COPD, pulmonary fibrosis, and cachexia [ 31 ]. These changes in body composition can lead to increased release of deposited compounds and, in our case, of toluene, ethylbenzene, and styrene.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline ESM CSA is a prognostic factor in patients with IPF 22,24 . Here, we demonstrated that the serial change in ESM CSA is also a prognostic factor in patients with IPF.…”
Section: Discussionmentioning
confidence: 99%
“…Miller et al reported that height-adjusted ESM CSA was significantly associated with 30-day mortality and length of hospital stay after lobectomy in patients with lung cancer 23 . Suzuki et al also revealed that a smaller ESM CSA in patients with IPF was associated with a poor prognosis 22 .…”
mentioning
confidence: 98%